Image enlargement research baised on anisotropic complex diffusion coupling to shock filter - Zhi-hong XI; Tao HAI (Tongxin xuebao)
In order to improve adaptability, the image enlargement method was proposed using improved anisotropic complex diffusion and adaptive Shock filter. For the enlargement of the noiseless image, an improved anisotropic com-plex diffusion was coupled to shock filter, which adaptively changes the diffusion threshold according to local variance, dividing diffusion time by the diffusion parameter of the image's imaginary part to remove the diffusion character dependence on the diffusion time, especially the linear diffusion character at the beginning of the diffusion. The noisy image was enlarged by using the adaptive threshold anisotropic complex diffusion filters according to pixel's local variance coupling with shock filters constrained by pixel's local variance to enhance the blurred edges. The adaptive threshold anisotropic complex diffusion detects the edge and noise through the combination of local variance and smoothed second derivative of the image, and the proposed method enhances the edge and smoothed the noise, containing the advantage of complex diffusion, as well as preserving the ramp structure and avoiding the staircase effective. The simulations prove prominent performance of the proposed method is not only for noiseless image but also for the certain gauss noisy image.